A companion to crime and deviance in the Middle Ages - Skoda, Hannah (ARC companions, 2023)
"This reference work examines the ways in which some medieval behaviours and identities were categorized as criminal or deviant. It also explores the implications of modern demonization of the Middle Ages. As well as discussing constructions of deviance, this book also explores the behaviours and identities which provoked these labels and processes. The model is one of reciprocity between behaviours and processes of demonisation and criminalisation. Each authoritative essay engages carefully with this approach, examining behaviours, the ways they were demonized, and the relationship between the two processes. The three parts of the volume are centred around forms of discursive and normative power—religious ideologies, political ideologies, and legalism. The authors also explore issues of political discourse, spiritual censure, justice and punishment, and the construction of taboos."